UPAYA DIKMAS LANTAS POLRES TEGAL GUNA MENGURANGI LAKA LANTAS DALAM RANGKA MEWUJUDKAN KAMSELTIBCAR LANTAS - Evan Adhi Pratama (Police Studies Review, 2022)
TEGAL RESORT POLICE EFFORT THROUGH TRAFFIC EDUCATION TO REDUCE TRAFFIC ACCIDENTS IN ORDER TO REALIZE TRAFFIC SAFETY EVAN ADHI PRATAMA, NO. AK 18,099, adhipratamaevan746@gmail.com Along with the times, the rate of increase in motorized vehicles continues to increase both in terms of number and technology. According to the Indonesian Central Statistics Agency, in 2020 the rate of motorized vehicles in Indonesia increased by 5.9% and every year in Indonesia motorized vehicles have increased by an average of 6.49%, but the increase in motorized vehicles is also followed by the number of traffic jams, violations, and traffic accidents. In terms of driving, there are still many Indonesian people who do not understand the proper and correct driving procedures. Most of these people can only drive without knowing good and correct driving procedures. This is a major factor in the occurrence of traffic accidents. The author limits the scope of the focus of writing by focusing on the object under study so that the problems discussed do not widen and the author uses a qualitative method in which the author focuses on problems that occur in the efforts of the Kamsel Unit in the implementation of social services and then in order to reduce the number of traffic accidents in the jurisdiction of the Tegal Police. . Seeing from the data that the author got, in the jurisdiction of the Tegal Police, there are still many traffic accidents that occur due to the number of traffic violations as well. In the application of this qualitative method, the author examines directly in the field, but not all events in the field are examined, only problems related to the object studied by the author. The author applies the concepts and theories that have been described previously where these concepts and theories will sharpen the author's analysis in focusing the problems that will be examined by the author. The Traffic Unit is the main implementing agency in the resort area under the Head of the Resort Police, led by Head of Traffic, Adjunct Police Commissioner Dwi Himawan Chandra, S.ik., M.M. So that the Tegal Police Traffic Unit is the main implementer of traffic problems in the Tegal Police jurisdiction.